Association Between Obstructive Sleep Apnea-Hypopnea Syndrome and Outcomes in Patients With Myocardial Infarction in the Absence of Obstructive Coronary Artery Disease - He, Chao-Jie; Cao, Lin-Feng; Zhu, Chun-Yan; Dai, Xiao-Ce; Yu, Yue-Yan; Zhu, Yu-Juan; Zhai, Chang-Lin; Qian, Gang; Hu, Hui-Lin (Frontiers in Cardiovascular Medicine, 2020)
Background and Aims: Myocardial infarction in the absence of obstructive coronary artery disease (MINOCA) occurs in 5–10% of all patients with acute myocardial infarction. Obstructive sleep apnea-hypopnea syndrome (OSAHS) is linked to increased cardiovascular morbidity and mortality, but the relationship of OSAHS and outcomes in patients with MINOCA remains unknown. We aimed to evaluate the association between OSAHS and clinical outcomes in patients with MINOCA. Methods: Between January 2015 and December 2016, we carried out a consecutive cohort study of 583 patients with MINOCA and followed them up for 3 years. An apnea-hypopnea index of ≥ 15 events per hour recorded by polysomnography was defined as the diagnostic criterion for OSAHS. The primary end point was all-cause mortality, and the second end point was major adverse cardiovascular or cerebrovascular events (MACCE), a composite of cardiac death, non-fatal myocardial infarction, heart failure, cardiovascular-related rehospitalization, and stroke. Results: All-cause mortality happened in 69 patients and MACCE occurred in 113 patients during the 3-year follow-up. Kaplan–Meier survival curves indicated the significant relationship of OSAHS with all-cause mortality (log-rank P = 0.012) and MACCE (log-rank P = 0.002). Multivariate Cox regression analysis indicated OSAHS as an independent predictor of all-cause mortality and MACCE [adjusted hazard ratio: 1.706; 95% confidence interval (CI): 1.286–2.423; P = 0.008; and adjusted hazard ratio: 1.733; 95% CI: 1.201–2.389; P < 0.001; respectively], independent of age, sex, cardiovascular risk factors and discharge medications. Conclusions: OSAHS is independently associated with increased risk of all-cause mortality and MACCE in patients with MINOCA. Intervention and treatment should be considered to alleviate OSAHS-associated risk.